Basic postulates of the new administrative-territorial structure of Ukraine - S. Kudelina; O. Nikolaieva; A. Hetmanenko; V. Khomutov (Kazimierz Wielki University, 2022)
The article is devoted to the study of the basic postulates of reforming the administrative-territorial structure of Ukraine. The authors proved that the regional volume of geographical support of this problem - informational, cartographic, geoinformational, scientific, pilot-project is much wider. The increased attention of geographers to the problems of the ATR and the new ATS is evidenced by the first dissertation developments and the growing flow of publications and scientific discussions on regionalization and administrative-territorial arrangement of the country.